“Preferred Reading” of Legal Texts - Škop, Martin (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
In the 1970s, British cultural theorist Stuart Hall introduced a concept known as preferred reading. It combines the ideological influence of mass media and dominant ways of understanding any text. This article focuses on mass media as a source of ideological background or context of legal interpretation and of any reading of legal texts. Law operates in culture and culture represents limitations in the law, according to the needs of dominant ideology. Culture introduces structures of domination which manipulate law. An important role is also given to popular culture and mass culture. These parts of the culture industry create borders in which the recipients (audience) think of law. Through mass media – rather than through other channels – dominant ideology infiltrates law. Legal consciousness is formed by dominant cultural frames formed by dominant ideology. Through this formation of mass media, law becomes a commodity. It shares the same values or contents as that of cultural industry and is the place where the theory of preferred reading can be introduced. According to the aforementioned theory, there are methods of interpretation that are more accurate than others are. This is simply because they lead to a result that is more preferred by ‘common opinion’ disseminated by mass culture.
Keywords: Hall, Stuart; lektura preferowana; interpretacja prawa